Choosing of drug for anesthesia in intensive therapy of traumatic disease for geriatric patients - Volkova, Yuliya; Sharlai, Kateryna; Boiko, Olena; Dmytriiev, Dmytro; Dmytriiev, Kostiantyn (My University, 2020)
OBJECTIVE: The aim of the study was to find the most rational approach to postoperative pain relief in the complex of intensive care for the acute and early periods of traumatic diseasein elderly patients. PATIENTS AND METHODS: Materials and methods: 132 gerontology patients with multiple trauma were included in the study. Respiratory and cardiovascular systems parameters were assessed, coagulogram and inflammatory response markers, pain severity and analgesia quality were assed. RESULTS: Results: According to the data obtained from the evaluation of VAS and Likerts scale, as well as other results, it was found that the use of NSAIDS and mu-opioid antagonists in the acute and early period of traumatic disease reduces significantly the severity of pain at a minimum daily dose (0.15 mg / kg), decreased the period of anaesthesia on demand, minimized negative respiratory and cardiovascular effects. Presence of sedative effect contributes to the improvement of emotional state of these patients. CONCLUSION: Conclusions: Age-related changes and concomitant pathology in geriatric patients define the need for the safe pain relief in this patients, in order to decrease possible adverse events. Optimal combination in geriatric patients with perioperative pain syndrome due to polytrauma is NSAIDs with antagonists-agonists. This combination reduce the prevalence and severity of negative respiratory and cardiovascular.
Keywords: pain; multiple trauma; gerontology patients